1995
DOI: 10.1128/jvi.69.1.60-68.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the murine AIDS-defective viral genome reveals a high reversion rate in vivo and a requirement for an intact Pr60gag protein for efficient induction of disease

Abstract: Pr60 gag appears to be the only protein encoded by the murine AIDS (MAIDS)-defective virus. To study the role of Pr60 gag or some other sequences of the viral genome in the pathogenicity of the virus, we have generated mutants of the defective viral genome. These mutant defective viruses, prepared as helper-free stocks, were inoculated into susceptible C57BL/6 mice. Mutant Du5H-A virus, which had a stop codon within gag MA(p15), did not induce target cell proliferation or MAIDS. Mutants Du5H-B and -C encoded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Currently proposed models suggest that lymphoproliferation associated with MAIDS locally involves the presence of: (1) the Pr60 gag protein encoded by the defective retrovirus genome; (2) B lymphocytes; and (3) CD4 + T cells [5,26,27]. Since the detection of the provirus renders likely the presence of the retroviral protein in the PP of infected mice, our results minimally suggest that either the PP microenvironment or the differentiation stage of PP lymphocytes locally modulates the lymphoproliferative process which is observed in the other lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently proposed models suggest that lymphoproliferation associated with MAIDS locally involves the presence of: (1) the Pr60 gag protein encoded by the defective retrovirus genome; (2) B lymphocytes; and (3) CD4 + T cells [5,26,27]. Since the detection of the provirus renders likely the presence of the retroviral protein in the PP of infected mice, our results minimally suggest that either the PP microenvironment or the differentiation stage of PP lymphocytes locally modulates the lymphoproliferative process which is observed in the other lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…If the MAIDS defective virus does not encode a classical SAG, how does it induce the severe immune defects seen in inoculated mice? The Pr60 gag fusion protein appears to be the only gene product encoded by the defective viral genome (1,23). Moreover, mutational analysis has shown that this protein is essential for the pathogenicity of the virus (23,25,38,47).…”
Section: Downloaded Frommentioning
confidence: 99%
“…A third mechanism to explain the immune disorders seen in MAIDS has been proposed previously. This model postulates that the immune deficiency syndrome arises as a paraneoplasic phenomenon, as a consequence of the proliferation and reprogramming of the infected B cells (23,25,28,30,31,49). These infected B cells could produce a new factor responsible for triggering the immune defects.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The defective viral genome does not harbor an oncogene and appears to encode a single protein, the Pr60 gag precursor (2,10,25). This protein and its location on cell membranes seem necessary and suffi-cient for the virus to induce rapid expansion of infected target cells (24,26,51). Initially, this proliferation is polyclonal, but it is clonal or oligoclonal in late stages of the disease (29).…”
mentioning
confidence: 99%